Community banking strategies : steady growth, safe portfolio management, and lasting client relationships - Boberski, Vincent; Wiley eBooks (Hoboken, N.J. : Wiley, 2010)
Praise for Community Banking Strategies. "In Community Banking Strategies, Vince Boberski not only gives unique and penetrating insights into the triggering events that caused the 'Great Recession' of 2008-2010, but also outlines effective and powerful forward-thinking strategies for community bankers to adopt as they cope with the new financial and market realities that lie ahead. This book is a must-read for any community banker wanting to take advantage of a generational shift in the financial markets and position the bank to thrive in future years."--Camden R. Fine, President and.
Chapter 9: Derivatives as a Way to Manage Balance Sheet, Earnings, and Business RiskAfterword; Appendix; About the Author; Index.
John Wiley and Sons
Keywords: Community banks; Community banks; BUSINESS & ECONOMICS -- Banks & Banking; Community banks; Electronic books